2007
DOI: 10.1029/2004wr003913
|View full text |Cite
|
Sign up to set email alerts
|

A simple model for predicting water table fluctuations in a tidal marsh

Abstract: [1] Wetland restoration efforts are ongoing in many urban estuaries. In this context the hydrologic characteristics of restored wetlands are of paramount importance since the spatially and temporally variable position of the water table and of soil saturation establishes the oxidation state of the substrate, which, in turn, affects the wetland's biogeochemical composition and the biological communities it is capable of supporting. A relatively simple analytical model developed here describes tidal marsh hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…The root zone sediments influence tidal infiltration and root water uptake and govern the mass transfer between these processes [Chapman, 1938b]. This perspective, focused on the root zone and its abiotic and biotic hydraulic properties, partially reconciles existing conceptual models of the salt marsh groundwater system as vertical flow due entirely to evapotranspiration and infiltration [Hemond and Fifield, 1982]; slow downward flow in the marsh interior feeding deep submarine groundwater discharge ; horizontal flow restricted to the channel banks, with no interior marsh flow [Harvey et al, 1987;Nuttle, 1988;Montalto et al, 2007]; or plant water uptake near channel banks controlling local water table position and unsaturated flow [Howes and Goehringer, 1994;Ursino et al, 2004;Wilson and Gardner, 2005;Li et al, 2005;Marani et al, 2006;Tosatto et al, 2009]. On the basis of the results of our detailed 3-D simulations, we conclude that each of these mechanisms is simultaneously significant in situ in different spatial regions of even a small marsh site and these different spatial regions can be usefully thought of as distinct ecohydrological zones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The root zone sediments influence tidal infiltration and root water uptake and govern the mass transfer between these processes [Chapman, 1938b]. This perspective, focused on the root zone and its abiotic and biotic hydraulic properties, partially reconciles existing conceptual models of the salt marsh groundwater system as vertical flow due entirely to evapotranspiration and infiltration [Hemond and Fifield, 1982]; slow downward flow in the marsh interior feeding deep submarine groundwater discharge ; horizontal flow restricted to the channel banks, with no interior marsh flow [Harvey et al, 1987;Nuttle, 1988;Montalto et al, 2007]; or plant water uptake near channel banks controlling local water table position and unsaturated flow [Howes and Goehringer, 1994;Ursino et al, 2004;Wilson and Gardner, 2005;Li et al, 2005;Marani et al, 2006;Tosatto et al, 2009]. On the basis of the results of our detailed 3-D simulations, we conclude that each of these mechanisms is simultaneously significant in situ in different spatial regions of even a small marsh site and these different spatial regions can be usefully thought of as distinct ecohydrological zones.…”
Section: Resultsmentioning
confidence: 99%
“…(2) Vertical flow in the marsh interior feeds deep, slow flow paths beneath the marsh that contribute to submarine groundwater discharge in the coastal zone . (3) Flow is horizontal and restricted to the few meters near the channel banks affected by rapid drainage; there is no lateral flow in the marsh interior because of low sediment permeability and zero groundwater head gradient [Harvey et al, 1987;Nuttle, 1988;Montalto et al, 2007]. (4) Plant root water uptake near channel banks controls local water table position and unsaturated flow [Howes and Goehringer, 1994;Ursino et al, 2004;Wilson and Gardner, 2005;Li et al, 2005;Marani et al, 2006;Tosatto et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…As the creek bank was vertical, the effect of a seepage face was negligible [33,46]. Therefore, the watertable exit point at the bank edge was assumed to be coupled with the tidal water level in the creek.…”
Section: Boundary and Initial Conditionsmentioning
confidence: 99%
“…Recent numerical studies examined the tidally induced pore-water flow and associated soil aeration conditions using various models including Boussinesq equation-based models [33,56], saturated flow models [15], Richards' equation-based (saturated and unsaturated flow) models [31,48,54,55,57,58,59] and air-water two-phase models [25,45]. These studies, which are mostly based on two-dimensional (2-D) cross-creek sections, aimed at quantifying the link between hydrological processes and vegetation dynamics in tidal marshes.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that these features are not unique for the study site, but are commonly found at natural coasts [e.g. Chaney and Stone, 1996;Montalto et al, 2007]. Therefore, it is important to study how nearshore groundwater flow and solute transport are affected by these features interacting with the tidal force.…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%